Implementasi Program Dandan Omah di Kelurahan Banyu Urip Kecamatan Sawahan Kota Surabaya - rahma thifal zahra arfila (Universitas Negeri Surabaya, 2026)
This study aims to describe the implementation of the Dandan Omah Program in Banyu Urip Village, Sawahan District, Surabaya City. This study uses a descriptive qualitative approach. Data collection techniques were carried out through interviews, observations, and documentation with informants from representatives of the Public Housing and Settlement Areas and Land Office of Surabaya City, the Banyu Urip Village Government, and the Rehabilitation Implementation Technical Group (KTPR). Data analysis was carried out using an interactive model through data collection, data presentation, and drawing conclusions. The analytical framework uses Richard E. Matland's (1995) implementation theory known as the Ambiguity-Conflict model. This model emphasizes two main dimensions in policy implementation, namely the level of Ambiguity and the level of Conflict. The results of the study indicate that the implementation of the Dandan Omah Program in Banyu Urip Village, Sawahan District, Surabaya City has generally run in accordance with the provisions stated in the Mayor's Regulation. The DPRKPP, the Village Office, and the KTPR Team carry out their respective roles according to established procedures, resulting in relatively low levels of conflict between formal actors. In practice, the problems that arise are not caused by unclear policy objectives or overlapping authority, but rather by the program implementation process in the field. Keywords: Program Implementation, Uninhabitable House, Banyu Urip Village.